2019
DOI: 10.1097/md.0000000000016575
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dapagliflozin as monotherapy in patients with type 2 diabetes mellitus

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 34 publications
1
29
0
2
Order By: Relevance
“…In a network meta-analysis of RCTs, all SGLT2is as monotherapy were statistically significantly more effective than placebo for reducing HbA 1c from baseline (range of mean differences: -0.59 to -1.23%), increasing the proportion of patients achieving target HbA 1c (odds ratio (OR) 2.18 to 3.45) and reducing mean body weight (range of mean differences -1.63 to -3.00 kg) 73 . Similar results were obtained in another meta-analysis devoted to RCTs with dapagliflozin used as monotherapy 74 . Aside from glucosuria and osmotic diuresis, sodium-glucose cotransporter type 2 inhibitors (SGLT2is) also induce some natriuresis, which is accompanied by intra-renal and intra-vascular effects.…”
Section: Monotherapysupporting
confidence: 86%
“…In a network meta-analysis of RCTs, all SGLT2is as monotherapy were statistically significantly more effective than placebo for reducing HbA 1c from baseline (range of mean differences: -0.59 to -1.23%), increasing the proportion of patients achieving target HbA 1c (odds ratio (OR) 2.18 to 3.45) and reducing mean body weight (range of mean differences -1.63 to -3.00 kg) 73 . Similar results were obtained in another meta-analysis devoted to RCTs with dapagliflozin used as monotherapy 74 . Aside from glucosuria and osmotic diuresis, sodium-glucose cotransporter type 2 inhibitors (SGLT2is) also induce some natriuresis, which is accompanied by intra-renal and intra-vascular effects.…”
Section: Monotherapysupporting
confidence: 86%
“…Although rare, genital infections were proportionately higher in dapagliflozin group than in the placebo group (0.9 vs. 0.1%; HR 8.36, 95% CI 4.19-16.68, p \ 0.001), both in men and in women in the DECLARE-TIMI 58 study [66]. A meta-analysis of six dapagliflozin RCTs showed a higher incidence of UTI with dapagliflozin compared with placebo [99]. However, a large meta-analysis of 109 studies involving SGLT2i found no difference in the incidence of UTI with SGLT2i compared with placebo (RR 1.02, 95% CI 0.95-1.09) [100].…”
Section: Genital Mycotic Infections and Utismentioning
confidence: 99%
“…Overall SGLT2i [100] Empagliflozin [58] Canagliflozin [98] Dapagliflozin [99] Acute kidney injury RR 0. [111].…”
Section: Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] A meta-analysis of six RCTs indicated that dapagliflozin monotherapy was effective in decreasing the levels of HbA1c, fasting plasma glucose (FPG) and body weight for patients with T2DM, and without raising hypoglycemia. [ 10 ] RCTs found that dapagliflozin could significantly lower the levels of HbA1c and FPG, and reduce overall glucose variability for T2DM patients that were inadequately controlled with insulin or metformin. [ 11 ] The latest study found that dapagliflozin could significantly lower the rate of cardiovascular death and the hospitalization for heart failure, but showed minimal effects in alleviating cardiovascular adverse events.…”
Section: Introductionmentioning
confidence: 99%